Phosphoinositide 3-OH kinase p85α and p110β are essential for androgen receptor transactivation and tumor progression in prostate cancers - Zhu, Q (2008)
Phosphoinositide 3-OH kinases (PI3Ks) are a group of major intracellular signaling molecules. In our previous study, we found that inhibition of PI3K activity suppressed the androgen receptor (AR)-mediated gene expression in prostate cancer cells. The AR has been considered as a critical determinant for the development and progression of human prostate cancers. In this study, we sought to identify the PI3K isoforms involved in AR transactivation. Using a gene-specific small interference RNA (siRNA) approach, we determined that the regulatory isoform p85α and the catalytic isoform p110β, but not p110α, were required for androgen-stimulated AR trans-activation and cell proliferation in prostate cancer cells. Consistently, overexpression of wild-type p110β but not p110α gene led to androgen-independent AR transactivation. Silencing p110β gene in prostate cancer cells abolished tumor growth in nude mice. Of the dual (lipid and protein) kinase activities, p110β’s lipid kinase activity was required for AR transactivation. Further analysis by a chromatin immunoprecipitation assay showed that p110β is indispensable for androgen-induced AR–DNA interaction. Finally, gene expression analysis of clinical specimens showed that both p85α and p110β were highly expressed in malignant prostate tissues compared to the nonmalignant compartments, and their expression levels correlated significantly with disease progression. Taken together, our data demonstrated that p85α and p110β are essential for androgen-stimulated AR transactivation, and their aberrant expression or activation might play an important role in prostate cancer progression.